(untitled) - Yutaka, Hirita (Cần Thơ, 2001)
This is a lucture for plant biotechnology of Mr. Yutaka Hirita. The lecture describes the biotechnology in plant improvement from the "Agricultural revolution at 10.000 years ago" to the Japanese biotechnology in 16th - 18th century".
Keywords: Plant biotechnology